(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Expectations, as anticipations of the present with respect to the aversion to the past and the propensity to the future, is the object of study of the present work and the objective was to specify a model for its study as a variable mediating the influence of the environment on behavior. A documentary study was carried out with a non-probabilistic selection of sources indexed to leading repositories in Latin America. A model was specified in which two hypothetical trajectories are proposed among the variables selected in the literature review. In that virtue, lines of investigation are noticed concerning the contrast of the mediating function of expectations.